A cohort study of age and sex specific risk of pyogenic liver abscess incidence in patients with type 2 diabetes mellitus - Ming-Chung Ko, - (Lippincott Williams and Wilkins Ltd., 2019)
To investigate the age-sex-specific incidence and relative risk of pyogenic liver abscess (PLA) in patients with type 2 diabetes mellitus (T2DM), and to assess the joint effects of T2DM and other clinical risk factors for PLA on PLA incidence. We used a population-based cohort design with Taiwan’s National Health Insurance claim data. Study subjects included 613,921 T2DM patients and 614,613 controls identified in 2000 and were followed to the end of 2010. Cox regression model was employed to calculate the hazard ratio (HR) and 95% confidence interval (CI) of PLA in relation to T2DM. Over an 11-year follow-up, 5336 T2DM and 1850 controls were admitted for PLA, representing a cumulative incidence of 0.87% and 0.30%, respectively. T2DM was significantly associated with increased hazard of PLA (HR, 2.88; 95% CI, 2.73–3.04). We also found that age and gender may significantly modify the relationship between T2DM and PLA, with a higher HR noted in males patients and those aged <45 years. Biliary tract diseases (HR, 8.60; 95% CI, 7.87–9.40) and liver cirrhosis (HR, 7.52; 95% CI, 6.58–8.59) may add substantially additional risk to the incidence of PLA in T2DM patients. The increased risk of PLA in T2DM was greater in male and younger patients. Careful management of biliary tract diseases and liver cirrhosis may also help reduce the incidence of PLA in T2DM patients.